Spatial and Canopy Utilization Pattern by Long-Tailed Monkeys (macaca fascicularis) Along the Oi Marai Tourist Trail - Dedy Rahman; Maiser Syaputra; Hasyyati Shabrina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The riparian ecosystem along the Oi Marai tourism trail in Tambora National Park constitutes a critical habitat for various wildlife species, including the Long-tailed Macaque (Macaca fascicularis). This study aims to analyze spatial use and canopy utilization by long-tailed macaques along the Oi Marai tourism trail in response to pressures from tourism activities. Data were collected using line transect and ad libitum sampling methods to record daily movements over a 14-day observation period. Spatial use was analyzed using the Minimum Convex Polygon (MCP) technique based on GPS coordinates. The results identified a single group of long-tailed macaques (Macaca fascicularis) consisting of 21 individuals led by one dominant male (alpha). The home range of this group was recorded at 3.60 ha, with daily travel distances ranging from 1.31 km to 5.52 km and a maximum ranging radius of 0.43 km. The territorial area covered 0.85 ha, with the farthest and nearest night sleeping position (NPS) distances recorded at 0.36 km and 0.03 km, respectively. The core area was estimated at 0.30 ha. Animal movements were predominantly concentrated along the river corridor due to the availability of water and food resources, including both natural forage and supplementary food provided by visitors. Vertically, canopy utilization exhibited functional stratification: strata C and D served as the primary zones for social activities and feeding (65%), whereas strata A and B functioned mainly as protective areas (20%). These findings indicate a reduction in home range size associated with the availability of supplementary food along the tourism trail.